The dendrochronological potential of some shrub species in Mongolian forest steppe - Dechinperlii, Enkhtuvshin; Vanjil, Gundegmaa; Mookhor, Khishigjargal; Purevdorj, Munkhsanaa (Mongolian Journal of Agricultural Sciences, 2023)
The impacts of land use changes and climate change on shrub expansion have been extensively documented in the Northern Hemisphere. Studies conducted in the Tibetan Plateau indicate that shrub expansion is more reliant on soil moisture than in the Arctic, where results indicate that changes in temperature and precipitation have a significant correlation with shrub expansion. Studies on the spread of shrubs throughout Central Asia, including the northern part of our country, are, unfortunately, insufficient. We carried out studies on 5 shrub species present in Shatan river area (Batsumber sum, Tuv aimag, Mongolia) to determine the response from climate factors and habitat types. According to the results of our research, there is a weak correlation (R2=0.24) between the morphological characteristics of the shrub. Also, depending on the type of habitat, the growth of annual rings is different for among growth habitats (df=2, F=13.5, P<0.0001). In addition, each species has different annual ring growth (df=4, F=8.63, P<0.0001). In terms of climatic factors, wind had a negative effect (R2=0.47), precipitation had a positive effect (R2=0.57) on the annual ring width of Salix divaricata, a shrub growing in river valley habitats, and it was weakly related to other species (df=2, F=13.5, P<0.0001). This differential pattern indicator may function depending on the habitat. That being the case, dominant shrub species in southwestern Khentii taiga, Mongolia have successfully been proven to have a high dendrochronological potential and it is practicable to apply it for rangeland and ecological assessments.